If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = -3x + 25 Reorder the terms: -3 + 6x = -3x + 25 Reorder the terms: -3 + 6x = 25 + -3x Solving -3 + 6x = 25 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + 6x + 3x = 25 + -3x + 3x Combine like terms: 6x + 3x = 9x -3 + 9x = 25 + -3x + 3x Combine like terms: -3x + 3x = 0 -3 + 9x = 25 + 0 -3 + 9x = 25 Add '3' to each side of the equation. -3 + 3 + 9x = 25 + 3 Combine like terms: -3 + 3 = 0 0 + 9x = 25 + 3 9x = 25 + 3 Combine like terms: 25 + 3 = 28 9x = 28 Divide each side by '9'. x = 3.111111111 Simplifying x = 3.111111111
| 20.16x+4.9x^2=0 | | 2m-(9m+6)m-7m=8 | | 1(3w-1)+2=18 | | 3x+2=100 | | 18=54/x | | 2+3sinx=0.5 | | 2x-7x-7=-5x+2-7 | | -3m-37-5(m-6)=6m-(9m-6)-8m+8 | | 2p+8q=36 | | 1/2x+5=3x-6 | | 10c+6d= | | 5x-10y=3 | | A-38=-10 | | 2x+4(2x-6)=2x+3(3x-7) | | 15x+12y=292.50 | | 6x+y=23 | | 0.5x+5=3x-6 | | 4(3x-1)=3(2x-6) | | 2x+2=-67 | | 2x-3=37-6x | | 4-x^2=x | | 2(a+3)=2-4a | | 2(3w-1)/2=18 | | 5(y-6)/3=-3y | | 170+x=-140 | | -9x-4=13-10x | | q=4gm+4z | | (8x-9)-(4x-1)=0 | | -x/7=14 | | 5/6m=90 | | y+97=2 | | -4x+y=-9 |